1998
DOI: 10.1046/j.1365-201x.1998.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell cyclic AMP in medullary thick ascending limb of Henle in a rat model of chronic renal failure

Abstract: Chronic renal failure (CRF) is accompanied by adaptive changes in electrolyte reabsorption in the thick ascending limb of Henle of surviving nephrons. To study the cellular mechanism of this adaptation, we measured intracellular cAMP in micro-dissected medullary thick ascending limb (mTAL) segments in rats with CRF. mTAL exhibited in CRF an increase of basal cAMP from 25.6 +/- 10.0 in controls to 65.8 +/- 11.3 fmol mm-1 tubule in CRF (P < 0.05). Vasopressin and calcitonin stimulated mTAL adenylate-cyclase in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In other pathological conditions, it has been described that DA does not modify Na + K + ATPase activity because some steps in the signaling cascade are disrupted. [37,38] In addition, previous results [39] have demonstrated that basal levels of intracellular cAMP in the microdissected mTAL are increased in this CRF model. Thus, vasopressin and calcitonin stimulated mTAL adenylate-cyclase in a dose-dependent manner in control rats but failed to stimulate it in CRF.…”
Section: Discussionmentioning
confidence: 92%
“…In other pathological conditions, it has been described that DA does not modify Na + K + ATPase activity because some steps in the signaling cascade are disrupted. [37,38] In addition, previous results [39] have demonstrated that basal levels of intracellular cAMP in the microdissected mTAL are increased in this CRF model. Thus, vasopressin and calcitonin stimulated mTAL adenylate-cyclase in a dose-dependent manner in control rats but failed to stimulate it in CRF.…”
Section: Discussionmentioning
confidence: 92%
“…The protocol was approved by the local Committee for Animal Research. Renal insufficiency was produced by suppressing a major portion of renal tissue, as described (2). Briefly, the left kidney was dipped in hot water for 14 s to burn the outer cortex.…”
Section: Methodsmentioning
confidence: 99%
“…Thus Bertuccio et al (1,2) showed an increase in intracellular cAMP levels in microdissected mTAL segments in chronic renal failure (CRF) rats, which were unresponsive to VP in vitro, opposed to baseline lower levels and a dose-response stimulation in control animals (1,2). Alternatively, Kwon et al (16) demonstrated compensatory increases in Na ϩ -K ϩ -Cl Ϫ cotransport expression per nephron in distal segments of the remnant kidney model (16).…”
mentioning
confidence: 99%